Efficient determinization of visibly and height-deterministic pushdown automata - Polách, Radomír; Trávníček, Jan; Janoušek, Jan; Melichar, Bořivoj (Computer languages, systems & structures, 2016)
New algorithms for the determinization of nondeterministic visibly and nondeterministic real-time height-deterministic pushdown automata are presented. The algorithms improve the results of existing algorithms. They construct only accessible states and necessary pushdown symbols of the resulting deterministic pushdown automata. •Tracking pushdown symbols which can appear on top of pushdown store for each state.•Generating pop (return) transition only for possible top pushdown symbols for each state.•Overall generating only accessible states and necessary pushdown store symbols.•Visibly pushdown automata determinization algorithm.•Height-deterministic (real-time) automata determinization algorithm.